HIDDEN VIEWS ON HOMEWORK: DO SOCIAL-NETWORKING SITES PROVIDE PARENTS WITH CYBER-AGENCY? - Lehner-Mear, Rachel (2017)
Whilst homework in primary schools is now commonplace, the maternal perspective on the homework support role is little understood because the issue is often masked in the de-gendered language of ‘parental involvement’ and ‘home-school partnerships’. This study takes a feminist approach to explore mothers’ views on homework by locating them in ‘hidden’ places on social-networking sites, asking whether these spaces give mothers cyber-agency in the homework discourse. A challenging, yet innovative, netnographic method is used to gather data from discussion ‘threads’ on two particular websites. The ethical issues surrounding the novel research method are discussed. The study uncovers opposing narratives on homework: rather than being released from dominant discourses in anonymous online spaces, many mothers remain influenced by prevailing ideologies of good mothering and core school values, whilst an emerging alternative narrative is identified, which is redefining the role of ‘the good mother’. The findings also question assumptions of online mother support networks, suggesting instead that mothers use the cyber-agency afforded by social-networking sites to position themselves as good mothers by criticising alternative approaches. This study is of interest to practitioners who wish to understand the impact of primary homework on mothers or to reconsider homework practices; and policymakers interested in widening the discourse on homework. Due to the original method applied to the research questions, researchers of both education and social-networking may be interested in what this study reveals about maternal cyber-agency and the ethics of online research.